Influence of particle fluorination on the stability of honey foam - Tyowua, Andrew T.; Echendu, Adebukola M.; Adejo, Sylvester O. (Frontiers in Soft Matter, 2023)
Honey foam has applications in food, cosmetic, and pharmaceutical industries. For example, honey foam can be used for bread or biscuit spread (food industry), as carriers of topical bioactive ingredients (cosmetic industry), or as carriers of drugs (pharmaceutical industry). However, the conditions for obtaining a stable honey foam remain unclear. In this study, we investigated the influence of particle fluorination on honey foam volume and foam stability by aerating natural (unadulterated) honey with fluorinated fumed silica (50 – 75% SiOH) or fluorinated sericite clay (PF-5 ‒ PF-12) particles. Higher foam volume (≤ 4.3 cm3) and foam stability (up to a year) were observed with the least (75% SiOH) fluorinated fumed silica particles while lower foam volume and foam stability were observed with the moderately (59% SiOH) and most (50% SiOH) fluorinated fumed silica particles. In contrast, regardless of the degree of fluorination, the fluorinated sericite clay particles yielded little (< 1 cm3) and unstable foam that collapsed completely within four weeks of preparation. Therefore, with respect to honey foam stabilization, fluorinated fumed silica particles are superior to fluorinated sericite clay particles. These foams can be used for topical formulation of cosmetic and pharmaceutical products, and our finding will guide future stabilization of honey foam for target applications.